Pervasive signaling - Bert Douglas Bernheim; Aaron L. Bodoh-Creed (Theoretical Economics, 2023)
How does the increasing publicness of decisions (due, for example, to social media) affect the total costs of social signaling distortions? While pervasive signaling may induce pervasive distortions, it may also permit people to signal while distorting each choice to a smaller degree. Ironically, for a broad class of environments, a sufficient increase in the number of signaling opportunities allows senders to ``live authentically'' – that is, to signal their types at arbitrarily low overall cost. This result survives when social networking technologies expand signaling opportunities and audience size in tandem, provided the returns to the latter are not too great.
Keywords: D82; 330; efficient information transmission; Multidimensional signaling; online social networks